The Effectiveness of ELT Practices in Government-Aided Schools (Rupandehi Campus Journal, 2025)
This study explores the current status of English Language Teaching (ELT) in government-aided public schools in Nepal by reviewing its historical development, including colonial influences and integration into the education system. Using a qualitative approach based on literature review and classroom observations, the study identifies several persistent challenges, such as reliance on outdated teaching methods like the Grammar-Translation Method, scarcity of teaching resources, and insufficient teacher training. The findings highlight the urgent need for reforms in ELT practices. To address these issues, the study recommends adopting communicative language teaching methods, integrating modern technologies into classrooms, enhancing teacher professional development, and improving the overall classroom environment to make English learning more effective in public schools.